Voltampérometrické stanovenie epinefrínu v ľudskom moči využitím bórom dopovanej diamantovej filmovej elektródy - Sochr, Jozef; Švorc, Ľubomír (Chemické listy, 2014)
An unmodified boron-doped diamond (BDD) electrode was used in combination with square-wave voltammetry (SWV) in a simple, rapid and inexpensive method for the detection and determinativ of adrenaline. A low detection limit of 2•107 mol l1 attained on BDD electrode was due to a very high signal-to-noise (S/N) ratio. The proposed procedure was applied to analysis of human urine spiked with adrenaline giving good recovery values. Matrix effects did not present any significant interference. BDD electrode may be used as a sensitive drug sensor in clinical analysis of various biologically active compounds and may replace complex and expensive chromatographic and spectral methods. Howe¬ver, the usefulness of this method can be limited in clinical analysis in the presence of other drugs in urine, e.g. ascorbic acid and uric acid.
Keywords: Electrochemical Techniques; diamant; Electrophoresis, Capillary; mydriatika; chromatografie iontoměničová; elektroforéza kapilární; sympatomimetika; Boron; vysokoúčinná kapalinová chromatografie; Urinalysis; lidé; chemické techniky analytické; Bronchodilator Agents; adrenalin; Diamond; Catecholamines; Adrenergic beta-Agonists; Chromatography, High Pressure Liquid; Electrodes; Sympathomimetics; elektrofyziologické jevy; Mydriatics; Epinephrine; analýza moči; Vasoconstrictor Agents; agonisté adrenergních beta-receptorů; Chemistry, Analytic; elektrochemické techniky; Adrenergic alpha-Agonists; vazokonstriktory; elektrody; Electrophysiological Phenomena; bor; agonisté adrenergních alfa-receptorů; analytická chemie; bronchodilatancia; Chromatography, Ion Exchange; katecholaminy; Chemistry Techniques, Analytical; Humans